Antidepressants are Independently Associated with Gait Deficits in Single and Dual Task Conditions - KENNY, ROSE (My University, 2015)
Objectives This study examined the relationships between late-onset depressive symptoms, antidepressants, and single and dual task gait in older adults. Design Cross-sectional study. Setting The Irish Longitudinal Study on Ageing (TILDA), a nationally representative cohort study. Participants Community-dwelling adults aged 60 years and older, with Mini-Mental State Examination score ≥24, no history of Parkinson's disease or early onset depression, and unaided completion of a gait assessment (N = 1,998). This study compared participants with and without potentially clinically relevant depressive symptoms (i.e., ≥16 on the Centre for Epidemiological Studies Depression scale) and participants who were and were not on antidepressant therapy. Measurements Gait measures were obtained during single and dual task (reciting alternate letters of alphabet, A-C-E) walking using a 4.88 m GAITRite walkway. Regression analysis was used to examine the associations between each group and gait adjusting for sociodemographics and health. Results In the unadjusted models, depressive symptoms and antidepressant use were associated with gait deficits. After adjusting for covariates, antidepressant use was associated with reduced gait speed and stride length in single and dual task walking; depressive symptoms were not associated with any deficits. Conclusions As gait impairments are associated with an increased risk of adverse outcomes including falls, clinicians should be aware of the impact of antidepressants on gait in older adults. Subsequent to this, interventions aimed at improving physical function, which is a known precursor to falls and functional disability, should be recommended.
PUBLISHED
Keywords: Depression; walking; falls; medication; Ageing; Neuroscience